The pragmatic orientation of paremiological unit in the literary text (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the paremiological units as units with programmed pragmatic effect that are not only representatives of typical situation and convey expressive atmosphere of literary text. They increase the stylistic effect and help to realize author’s efforts. Also they harmonize prose text and make it more rhythmical and melodious.
Keywords: text; paremiological unit; pragmatic effect; function; sound reiteration; lexical reiteration